2019
DOI: 10.1136/bmjopen-2019-029017
|View full text |Cite
|
Sign up to set email alerts
|

Role ofFAM19A4/miR124-2methylation analysis in predicting regression or non-regression of CIN2/3 lesions: a protocol of an observational longitudinal cohort study

Abstract: IntroductionThe clinical course of high-grade cervical intraepithelial neoplasia (CIN2/3) is characterised by a high spontaneous regression rate. Histological assessment is unable to differentiate between CIN2/3 lesions likely to regress and those likely to persist or progress. Most CIN2/3 lesions are treated by surgical excision, leading to overtreatment of a substantial proportion. In this prospective study, we evaluate the value of DNA methylation of host cell genes, which has shown to be particularly sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…23 In addition, a negative FAM19A4/miR124-2 methylation test in HPV-positive women provided a very low 14-year cervical cancer risk. 42 In agreement with the latter finding, preliminary results of the CONCERVE study 22 show that women with CIN2/3 with a negative FAM19A4/miR124-2 methylation test have a higher regression rate than women with a positive methylation test (Kremer, Dick, Meijer et al, unpublished data, manuscript in preparation). Therefore, it is assumed that methylation-positive CIN2/3 lesions have a higher short-term progression risk to cervical cancer than methylationnegative CIN2/3 lesions.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…23 In addition, a negative FAM19A4/miR124-2 methylation test in HPV-positive women provided a very low 14-year cervical cancer risk. 42 In agreement with the latter finding, preliminary results of the CONCERVE study 22 show that women with CIN2/3 with a negative FAM19A4/miR124-2 methylation test have a higher regression rate than women with a positive methylation test (Kremer, Dick, Meijer et al, unpublished data, manuscript in preparation). Therefore, it is assumed that methylation-positive CIN2/3 lesions have a higher short-term progression risk to cervical cancer than methylationnegative CIN2/3 lesions.…”
Section: Discussionsupporting
confidence: 54%
“…identification of transforming CIN lesions, as well as the potential to predict regression and/or progression of CIN lesions. 21,22 Furthermore, methylation analysis has demonstrated that CIN2/3 lesions associated with a persistent HPV infection of at least 5 years had cancer-like methylation patterns, suggesting a high short-term progression risk to cervical cancer. 23,24 Methylation analysis in combination with immunohistochemical staining of p16 ink4a , Ki-67 and E4 might provide biomarker profiles that could improve the clinical guidance in women with high-grade CIN to prevent overtreatment of regressive lesions and potential obstetric complications.…”
Section: What's New?mentioning
confidence: 99%
“…Indeed, it was recently shown that a methylation panel consisting of host cell and viral genes has the ability to identify progressive CIN2 lesions in young women [28]. Additional studies are presently ongoing to validate these findings [29].…”
Section: Discussionmentioning
confidence: 93%
“…High methylation of host cell marker EPB41L3 combined with viral methylation markers (S5 classifier) were associated with progression to CIN3. A similar study is ongoing in the Netherlands, evaluating the value of FAM19A4/miR124‐2 methylation in the prediction of regression or non‐regression in untreated women 81 . This study also includes women with CIN3 and women aged up to 55 years.…”
Section: Use Of Methylation Analysis In Cervical Screeningmentioning
confidence: 99%